STUDY OF CESIUM AND STRODIUM UPTAKE BY ELECTRON AND GAMMA IRRADIATED CLINOPTILOLITE - Μωραίτης, Δ.; Χρηστίδης, Γ.; Keheyan, Y.; Akhalbedashvili, L.; Kekelidze, N.; Gerokyan, R.; Yeritsyan, H.; Sargsyan, H. (Bulletin of the Geological Society of Greece, 2004)
Clinoptilolite is widely known for their uses especially in environmental applications. They have been utilized.in nuclear wastewater treatment and in land restoration. Irradiation emitted by nuclear liquid waste includes α, β and γ radiation. Irradiated clinoptilolite may exhibit crystal changes which affect the sorption of Cs+ and Sr2*. Sorption experiments with Cs+ and Sr2* were carried out separately. Solutions containing various concentrations of each element were brought in contact with untreated or irradiated (electron irradiation 1014 1015 e/cm2 and y-irradiation 70 Mrad) Armenian clinoptilolite. Additional experiments were carried out with solutions containing both Sr and Cs in varying proportions (75/25%, 50/50%, 25/75%) and concentrations (0.5 χ CEC and 2x CEC). The later types of experiments were contacted with untreated and irradiated Armenian clinoptilolite (yirradiation 70 Mrad, electron irradiation 1014 e/cm2). In solutions containing one ion (either Sr21 or Cs+), there is a slight increase of Cs+ uptake in the highest loadings of Cs (2x CEC, 1x CEC) for the γ-irradiated material. Electron Irradiation (1015 e/cm2) has not affected the sorption of Cs+. Clinoptilolite treated with y-irradiation exhibits decrease in Sr2* uptake and, equilibrium is attained at a significantly greater reaction time, especially when compared to Cs+. In binary solutions (Sr^-Cs*), clinoptilolite absorbs larger amounts of Cs+ compare to Sr2* and Cs+ uptake is instant compare to Sr2* where a delay is observed. There is a decrease in Sr2* sorption and an apparent delay in attaining equilibrium after y-irradiation. The same effects have been observed in the sorption of Sr2* after electron irradiation. Cs+ uptake has not been affected after clinoptilolite treatment with electron irradiation and y-irradiation.